First-in-Human Integrated Use of a Dedicated Microsurgical Robot with a 4K 3D Exoscope: The Future of Microsurgery - Tom J. M. van Mulken; Shan S. Qiu; Yasmine Jonis; Jairo J. A. Profar; Taco J. Blokhuis; Jan Geurts; Rutger M. Schols; René R. W. J. van der Hulst (Life, 2023)
Innovative techniques can help overcome the limitations of the human body. Operating on very small structures requires adequate vision of the surgical field and precise movements of sophisticated instruments. Both the human eye and hand are limited when performing microsurgery. Conventional microsurgery uses operation microscopes to enhance the visualization of very small structures. Evolving technology of high-definition 3D cameras provides the opportunity to replace conventional operation microscopes, thereby improving ergonomics for surgeons. This leaves the human hand as a limiting factor in microsurgery. A dedicated robot for microsurgery has been developed to overcome this limitation and enhance the precision and stability of the surgeons’ hands. We present the first-in-human case in reconstructive microsurgery where both technologies are integrated using a dedicated microsurgical robot in combination with a 4K 3D exoscope.